Продовольча безпека у глобальному вимірі: фактори забезпечення та сучасні тренди - Кузьома, Віталій Вікторович (Національний технічний університет "Харківський політехнічний інститут", 2024)
Питання забезпечення глобальної продовольчої безпеки залишається одним з основних та вирішальних для всіх без виключення країн світу. Реалізація цілей сталого розвитку, які стали стратегічним пріоритетом для суспільства, відокремили проблеми подолання голоду та забезпечення здоров’я населення ключовими та у якості головного пріоритету подальшого існування людства. У статті досліджено сутність категорії «продовольча безпека» з різних науково-методичних позицій, проведено комплексний огляд основних тенденцій, які супроводжують аспекти вирішення питання досягнення продовольчої безпеки у світовому масштабі. Відокремлені основні елементи агропродовольчої системи, як ресурсного базису для забезпечення глобальної продовольчої безпеки. Виявлено сукупність ключових факторів, які здійснюють вплив на можливості забезпечення глобальної продовольчої безпеки. Окреслено архітектура моделі, які містить базові характеристики досягнення стану глобальної продовольчої безпеки. Виявлено та надано оцінка ключовим трендам на шляху досягненні глобальної продовольчої безпеки. Визначено, що Україна є потужним гравцем світового агропродовольчого ринку та має потужний потенціал сприяння забезпеченню подолання глобальної проблеми голоду у світі. Виняткова та основна умова для цього – це завершення військового конфлікту на території України та відновлення ресурсного і виробничого потенціалу сільського господарства країни на засадах подальшого сталого розвитку.

The issue of ensuring global food security remains one of the leading and decisive issues for all countries in the world, without exception. The implementation of the goals of sustainable development, which have become a strategic priority for society, has separated the problems of overcoming hunger and ensuring the health of the population as key and the main priority for the further existence of humanity. The article examines the essence of the category "food security" from various scientific and methodological positions and conducts a comprehensive review of the prominent trends that accompany the aspects of solving the issue of achieving food security on a global scale. The main elements of the agro-food system as a resource base for ensuring global food security are separated: 1) a sufficient amount of safe, high-quality food; 2) healthy nutrition of the population; 3) inclusive distribution of income and expenses of the population; 4) prevention of climate change, sustainability and conservation of biological resources. A set of key factors influencing the possibilities of ensuring global food security has been identified: population size, science and technology, climate change, imperfect global food distribution mechanisms, problems of gender inequality, urbanization processes, and inclusive gaps between the living conditions of the population, the growing scale of political and military conflicts The model's architecture, which contains the essential characteristics of achieving global food security, is outlined. Critical trends for achieving global food security were identified and assessed. Among them: the relative stability of the problem of world hunger, in particular, in individual world regions; increasing the level of dependency, hunger, and gender inequality; the growth of inclusive gaps in the economic availability of food; increase in the level of urbanization of the population; the health problem of a large part of the world's population and the strengthening of the trend of healthy eating. Ukraine, a significant player in the global agri food market, holds substantial potential to combat the world's hunger crisis. The key to unlocking this potential lies in resolving the ongoing military conflict within Ukraine's borders and restoring the country's agricultural resources and production capabilities through sustainable development.
Global food security: security factors and current trends
Keywords: агропродовольче виробництво; сільське господарство; голод; продовольча безпека; розвиток; суспільство; agro-food production; agriculture; hunger; food security; development; society